(3CNHGQ hCTYGQ hfhGOQ hedM habQ hMce hhUGjG oefJNHIs - (3jGbhJ Hf YHO Gddg GdeSJYUej,J (B698 (3g` s
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3fYeJGf eZHhf ajgeG cKjQ ef GdfGS(B: (3GdUMI hGdaQGZ s
(3BNQgG (B:s
(3bGd GdMSf Hf Ydj (B((3YdjgeG GdSdGe(B): (3CLeY cCfc JYjT CHOkG, haQb cCfc JehJ ZOG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B157s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B9 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs